2020
DOI: 10.1038/s41467-020-18661-9
|View full text |Cite
|
Sign up to set email alerts
|

The social and environmental complexities of extracting energy transition metals

Abstract: Environmental, social and governance pressures should feature in future scenario planning about the transition to a low carbon future. As low-carbon energy technologies advance, markets are driving demand for energy transition metals. Increased extraction rates will augment the stress placed on people and the environment in extractive locations. To quantify this stress, we develop a set of global composite environmental, social and governance indicators, and examine mining projects across 20 metal commodities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
117
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(118 citation statements)
references
References 33 publications
(43 reference statements)
0
117
0
1
Order By: Relevance
“…The move towards a low-carbon economy is projected to lead to increased demand for minerals including cobalt, lithium, nickel, copper, vanadium and indium for use in electric vehicles (EVs), green energy technologies and storage batteries, with large increases in demand predicted for cobalt, nickel and lithium (Teske, 2019;World Economic Forum, 2019;Hund et al, 2020). Interest in mining virgin resources from the deep sea has, in part, been driven by such projections, alongside desires to maintain a diversity of supply and concerns about environmental and human rights impacts associated with terrestrial mining (Church and Crawford, 2020;Lèbre et al, 2020;Paulikas et al, 2020b).…”
Section: The Perceived Benefits and Risks Of Deep-sea Mining The Argued Need For Deep Seabed Mining To Supply Minerals For The Green Revomentioning
confidence: 99%
“…The move towards a low-carbon economy is projected to lead to increased demand for minerals including cobalt, lithium, nickel, copper, vanadium and indium for use in electric vehicles (EVs), green energy technologies and storage batteries, with large increases in demand predicted for cobalt, nickel and lithium (Teske, 2019;World Economic Forum, 2019;Hund et al, 2020). Interest in mining virgin resources from the deep sea has, in part, been driven by such projections, alongside desires to maintain a diversity of supply and concerns about environmental and human rights impacts associated with terrestrial mining (Church and Crawford, 2020;Lèbre et al, 2020;Paulikas et al, 2020b).…”
Section: The Perceived Benefits and Risks Of Deep-sea Mining The Argued Need For Deep Seabed Mining To Supply Minerals For The Green Revomentioning
confidence: 99%
“…The size of future stocks and flows are uncertain and have been disputed for long due to diverging assumptions on, e.g. (Northey et al 2017;Odell et al 2018) and increased risk of social instability due to environmental degradation (Lebre et al 2020). This study has identified a new source of uncertainty, namely how mitigating climate change can reduce the use of host resources and thereby reduce primary supply of by-products.…”
Section: Uncertainties With Estimating Future Stocks Potential Flows and Recovered Flowsmentioning
confidence: 99%
“…They propose a multi-criteria classification of all risks to systematically incorporate them into risk and impact assessments at the scale of the mining territory. The authors recommend a detailed preliminary analysis of mining projects up to their technical and operational characteristics, taken as decisive factors that will influence the nature and intensity of the potential impacts at various scales, and thus help make decisions at the territorial level, [36] also advocate for a broader Copyright © Michel Cathelineau AMMS.MS.ID.000625.5 (5).2020 vision to be integrated into future scenario planning about the transition to a low carbon future, by systematically considering in risk quantification, the environmental, social and governance (ESG) pressures surrounding the point of extraction (i. e. mining territories at large). The study presents a global assessment of ESG complexities associated with the extraction of Energy Transition Metals (ETM).…”
Section: Mining Industry and Civil Society: The Challenges Of Complex Interactions And The Opportunity Of Sustainabilitymentioning
confidence: 99%